ISLAM TRANSNASIONAL : TANTANGAN BAGI MODERASI BERAGAMA DI INDONESIA - Nasir, Muhammad; Khusairi, Abdullah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat of Institut Agama Islam Negeri Metro, 2024)
This article discusses the impact and challenges of Transnational Islamic groups on strengthening Religious Moderation in Indonesia in promoting a balanced, tolerant and peaceful understanding of Islam, both at the local and global levels. This article was written using the exposition report method which relies on the strength of the author's opinion in reviewing literature facts about Transnational Islam and Religious Moderation in Indonesia. The concepts of Transnational Islam and Religious Moderation in this article are positioned in a face-to-face relationship, where Transnational Islam is positioned as a challenge for strengthening Religious Moderation in Indonesia. This article concludes that Transnational Islamic Groups, which in terms of ideology and religious practices contain a spirit of religious exclusivism, exclusivism, and violent extremism, are a challenge to religious moderation in Indonesia. These three spirits were formulated by the religious moderation program with the abbreviation REEVE. Based on these three challenge formulations, it can be understood that Strengthening Religious Moderation as a public policy is the Indonesian government's response to exclusive, extreme and radical religious practices which have a negative impact on the harmonization of social life in society and at the same time endanger the integrity of the Republic of Indonesia.